Randomized Phase II Study of Cabazitaxel Versus Methotrexate in Patients With Recurrent and/or Metastatic Squamous Cell Carcinoma of the Head and Neck Previously Treated With Platinum-Based Therapy. (30th November 2016) - Machiels, Jean-Pascal Henry; Van Maanen, Aline; Vandenbulcke, Jean-Marie; Filleul, Bertrand; Seront, Emmanuel; Henry, Stéphanie; D'Hondt, Lionel; Lonchay, Christophe; Holbrechts, Stéphane; Boegner, Petra; Brohee, Dany; Dequanter, Didier; et al.
Abstract : Lessons Learned : Cabazitaxel has activity in squamous cell carcinoma of the head and neck (SCCHN) and taxane-resistant cell lines. For the first time, cabazitaxel was investigated in incurable patients with recurrent SCCHN. Patients were randomly assigned to cabazitaxel every 3 weeks or weekly methotrexate. This phase II study did not meet its primary endpoint. Cabazitaxel has low activity in SCCHN. The toxicity profile in this population also was not favorable owing to the high rate of febrile neutropenia observed (17%). Background: Cabazitaxel is a second-generation taxane that improves the survival of patients with metastatic castrate-resistant prostate cancer following docetaxel therapy. Cabazitaxel has activity in squamous cell carcinoma of the head and neck (SCCHN) and taxane-resistant cell lines. In this randomized phase II trial, we investigated cabazitaxel in patients with recurrent SCCHN. Methods: Patients with incurable SCCHN with progression after platinum-based therapy were randomly assigned to cabazitaxel every 3 weeks (cycle 1, 20 mg/m 2, increased to 25 mg/m 2 for subsequent cycles in the absence of nonhematological adverse events [AEs] greater than grade 2 and hematological AEs greater than grade 3) or methotrexate (40 mg/m 2 /week). The patients were stratified according to their performance status and previous platinum-based chemotherapy for palliation versus curative intent. The primary endpoint was the progression-free survival rate (PFSR) at 18 weeks. Results: Of the 101 patients, 53 and 48, with a median age of 58.0 years (range, 41–80), were randomly assigned to cabazitaxel or methotrexate, respectively. The PFSR at 18 weeks was 13.2% (95% confidence interval [CI], 5%–25%) for cabazitaxel and 8.3% (95% CI, 2%–20%) for methotrexate. The median progression-free survival was 1.9 months in both arms. The median overall survival was 5.0 and 3.6 months for cabazitaxel and methotrexate, respectively. More patients experienced serious adverse events with cabazitaxel than with methotrexate (54% vs. 36%). The most common drug-related grade 3–4 AE in the cabazitaxel arm was febrile neutropenia (17.3%). Conclusion: This study did not meet its primary endpoint. Cabazitaxel has low activity in recurrent SCCHN.